VIABILITAS DAN VIGOR BENIH AKIBAT DETERIORASI - Jasmi Jasmi (Jurnal Agrotek Lestari, 2018)
This study aims to study the decline of seeds using a saturated salt solution and to regulate the moisture of the storage space. This research was conducted by Plant Science Laboratory, Gadjah Mada University. Materials and tools used in this research are soybean seed, NaBr salt, NaCl and aquades. Tools used include tub germination, measuring cups, pumpkin glasses, petridis and gauze. Trial using 3x3 Factorial Design compiled in Completely Randomized Design with 4 replications. Factor I is a water content consisting of 2 levels, namely: a) Water content of seeds 9%, b) Water content of 13% seed. Factor II is a relative humidity (RH) of storage space comprising 2 levels: a) Saturated NaBr salt solution (80%), b) Saturated NaCl salt solution (40-50%). Observations observed were seed sprouts once per week seeds expressed in percent, seedling growth (seed height, fresh weight of seedlings, dry weight of seed, stem diameter and number of leaves). The results showed that the percentage of seedlings or seedlings in the 80% and 45% moisture content of the soilmoisture content of 9% with two weeks of storage duration, while the humidity 80% and 45% with the water content of 13% The lowest in two weeks storage time. However, with four weeks storage showed reduced seed viability at both 80% and 45% moisture and 13% and 9% water content. The result of the analysis showed that the height of the seedlings, the number of leaves, the fresh weight and the dry weight on the control significantly influenced all treatment based on the t-test.Keywords: Detioration, long save, seed viability, soybean